The Effect of Influencer Marketing on Purchase Decisions of Chaca Burgo Makassar Branch - Arismaleo, Andi Rifqih; Amin, Andi Mustika; Wardhana Haeruddin, Muhammad Ilham; Hasbiah, Siti; Musa, Muh. Ichwan (Economics and Business Journal (ECBIS), 2023)
Advances in technology such as the presence of social media require companies to be able to adjust in carrying out their activities such as marketing using influencer marketing. This study aims to determine the effect of influencer marketing on purchasing decisions for the Makassar branch of Chaca Burgo. This research uses qualitative methods by conducting observations, questionnaires, and interviews. Data were analyzed using a simple linear regression analysis method that used SPSS data processing results to prove the hypothesis. The results showed that the influencer marketing variable had a positive and significant effect on the purchasing decision variable. So that the better influencer marketing is in carrying out promotions, the purchasing decisions by consumers will increase.